Exegesis and Screenplay for a Film Entitled: White Magnolia - Hong, Ki Myung (Auckland University of Technology, 2009)
Most new migrants choose New Zealand as their second home country because New Zealand provides peaceful, safe and relaxed life style and also quality education compared to their homelands. However, for most migrants, settling down in New Zealand is one of the most dynamic and complex processes in their lives. Many migrants are struggling to adjust to New Zealand because the expression of cultural values is different in New Zealand than in their cultures. As migrants adjust to the new culture, their traditional cultural values are increasingly challenged by New Zealand cultural values leading to some degree of personal change. As a result, most immigrants encounter many unfamiliar cultural values in the initial stage of immigration to a New Zealand culture. This story is about the impact of culture-shock on an ordinary Korean migrant family and their struggle adjusting in a new society.
Keywords: Immigrants; Culture; Screenplay; Drama